EFL teachers' perceptions and practices towards delivering corrective feedback on young learners' writing performance : - Lê, Nguyễn Thảo Trinh (Trường đại học Cần Thơ, 2018)
The study aims to investigate what EFL teachers think about corrective feedback and how they deliver it to young learners in writing skills. The study aims at: (1) investigating teachers’ perceptions of using corrective feedback; and (2) figuring out how teachers deliver corrective feedback. From the aims given, the research aimed to answer the following questions: What are EFL teachers’ perceptions of delivering corrective feedback on young learners’ writing? How do they deliver corrective feedback on young learners’ writing?